2013
DOI: 10.1007/s11046-013-9691-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dermatophyte PCR Kit with Conventional Methods for Detection of Dermatophytes in Skin Specimens

Abstract: The laboratory diagnosis of dermatophytosis is usually based on direct microscopic examination and culturing of clinical specimens. A commercial polymerase chain reaction kit (Dermatophyte PCR) has had favorable results when used for detection of dermatophytes and identification of Trichophyton rubrum in nail specimens. This study investigated the efficacy of the Dermatophyte PCR kit for detecting dermatophytosis in 191 hair or skin specimens from patients with suspected dermatophytosis. PCR was positive for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
3
11
0
1
Order By: Relevance
“…The DNA extraction method used was modified from a previous method [10,19,21]. Consistent with previous studies [22,23], we found that the process of bead beating improves the efficiency of DNA isolation from culture strains (data not shown).…”
Section: Discussionsupporting
confidence: 84%
“…The DNA extraction method used was modified from a previous method [10,19,21]. Consistent with previous studies [22,23], we found that the process of bead beating improves the efficiency of DNA isolation from culture strains (data not shown).…”
Section: Discussionsupporting
confidence: 84%
“…The most significant finding in this study was the rapid identification of dermatophyte species in clinical samples from Arabian horses directly from hair samples utilizing a PCR method. Previous reports have described PCR‐based assays that either identify only one or a few dermatophyte species or are unable to identify dermatophytes to the species level, or are not used directly on clinical material . Some studies have used nested or semi‐nested PCR or double‐round PCR, which are known to have a high risk of contamination .…”
Section: Discussionmentioning
confidence: 99%
“…PCR, a primary technique of DNA‐based analysis, can also be conducted using a real‐time protocol to quantify the relative levels of the transcript and estimate the viability of the sample, and it takes less time than cultures . Moreover, in a study comparing real‐time PCR with conventional diagnostic methods, real‐time PCR provided 100% sensitivity and 82% specificity, and had significantly fewer false‐negative results than conventional diagnostic methods . Real‐time PCR has excellent sensitivity and specificity, but unlike PCR‐REBA, it cannot determine a number of species at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…3,14 Moreover, in a study comparing real-time PCR with conventional diagnostic methods, real-time PCR provided 100% sensitivity and 82% specificity, and had significantly fewer false-negative results than conventional diagnostic methods. 15,16 Real-time PCR has excellent sensitivity and specificity, but unlike PCR-REBA, it cannot determine a number of species at the same time. In vivo reflectance confocal microscopy and the fungal fluores- cence method can be used to diagnose dermatophytic infection, but they require expensive equipment and extensive technical training.…”
Section: Discussionmentioning
confidence: 99%